Efforts to Improve Health Cadres' Roles in Posbindu Management - Udin Rosidin; Ahmad Yamin; Mamat Lukman; Iwan Shalahuddin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Health development aims to increase awareness, will and ability to live healthily for everyone in order to achieve the highest possible level of health. Simultaneously with the implementation of health development, various health problems emerged. One of the factors that triggers health problems is the lack of public awareness of clean and healthy living habits. The results of a survey conducted by the community service team in Kota Wetan Village revealed several health problems such as high cases of hypertension and a lack of clean and healthy living behavior. These behaviors include rarely doing physical activity, consuming foods high in sugar, salt and fat. Apart from that, the implementation of Posbindu in Kota Wetan Village is still not optimal. Based on this, the initial level intervention to overcome the above problems is the implementation of posbinndu in each RW. Posbindu can run well if health cadres as posbindu managers have the knowledge and skills in managing posbindu. Taking these problems into account, the agreed intervention was the implementation of training for health cadres in optimizing the role of health cadres as posbindu managers. The aim of the activity is to increase the knowledge and abilities of health cadres in managing posbindu. The results of the activity showed that the average knowledge value before the activity was 61 points and the average value after the activity was 89 points. There was an increase in knowledge after health education was carried out by 28 points. The follow-up plan for this activity is that it is hoped that the Guntur Community Health Center will be able to carry out training activities for cadres on a regular basis. It is hoped that Kota Wetan Village will continue to provide support, so that the programs that have been implemented will continue to run